THE CONCEPT OF SOLIDARITY FROM THE PHILOSOPHICAL THOUGHT OF THE LAW OF JESÚS GONZÁLEZ AMUCHASTEGUI - Garcia Gómez, Jainer Enrique (2019)
The following research aims to determine, the construction of the concept of solidarity from a vision of the philosophy of law Jesús González Amuchastegui. To reach, the research uses the hermeneutic method, this looks for the origin, source and elements of the construction of the concept in the author. An analysis and study of the arguments and supports used by Amuchastegui to talk about solidarity in his vision as a philosopher of Law. The construction of the concept of Amuchastegui was taken from the Law and with elements of Louis Blanc, this integrated the social dimension of the individuals, a conciliation between the particular interests and the collective interests, a harmony between freedom, society and fraternity or solidarity becoming an opposition to selfish prejudice or possessive individualism to achieve a development of individual autonomy.